EXPERIENCE IN DEVELOPMENT MEDICAL KITS FOR MEDICAL SERVICES OF THE RUSSIAN FEDERATION ARMED FORCES - E. O. Rodionov; Yu. V. Miroshnichenko; V. N. Kononov; A. V. Tikhonov; I. V. Klochkova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Introduction. The development of modern, complete-standard issue equipment for the Armed Forces Medical Service is an urgent organizational and management task. First aid kits, medical bags, sets of medical equipment, medical kits and packing existed until recently; no longer meet modern requirements for a number of objective reasons. The aim of the study was the formation of programs of development of modern samples of complete-standard-issue equipment. Materials and methods. The study was conducted based on the analysis of scientific literature and guidelines which regulate different aspects of the Armed Forces Medical Service complete-standard issue equipment. The study used methods like: retrospective, content analysis, comparison and description, logical, structural and functional analysis, expert assessments, decision-making, as well as the methods of the theory of constraints and other systems. Results and discussion. rmation of the range of medical property in modern conditions for inclusion into complete-standard issue equipment is connected with the need to make timely decisions on choosing the most efficient models, taking into account market conditions and economic opportunities. There are requirements established for the complete-samples standard issue equipment for their use outside a medical organization. Development program structure of complete-standard-issue equipment is shown, as well as examples of the formation of the content of medical equipment kits. On the basis of the offered program a new complete-standard issue equipment of the Armed Forces Medical Service was created. In accordance with the principles of the theory of constraints a strategy to optimize the composition of sets of medical equipment was developed. It included comprehensive solutions aimed at stabilizing the activity of the pharmaceutical industry in the interest of the Armed Forces Medical Service. Conclusions. An offered program has allowed developing new models of complete-standard issue equipment of the Armed Forces Medical Service, which provides healthcare to a necessary extent and speed of deployment and mobility of medical units formations and military units in the field.